2003
DOI: 10.1002/cncr.11168
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for local recurrence of small hepatocellular carcinoma tumors after a single session, single application of percutaneous radiofrequency ablation

Abstract: This work is aimed to provide a systematic design procedure to determine the process configuration, the relative position of the reactive zone, and separation sections. Instead of investigating real chemical systems, ideal chemical reaction systems with different relative volatility rankings will be studied. This provides a gradual transition as the reaction and separation properties change. The reaction considered is a reversible reaction, A + B ⇔︁ C + D, and this constitutes a quaternary system with 24 (4) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
190
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(217 citation statements)
references
References 46 publications
20
190
2
5
Order By: Relevance
“…Komorizono and colleagues reported that the tumor of more than 2 cm in size and the subcapsular lesions were the risk factors of local tumor recurrence [13] . In our study, tumor size >2 cm has the trend for early local tumor recurrence (P = 0.089, Mann-Whitney test) ( Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Komorizono and colleagues reported that the tumor of more than 2 cm in size and the subcapsular lesions were the risk factors of local tumor recurrence [13] . In our study, tumor size >2 cm has the trend for early local tumor recurrence (P = 0.089, Mann-Whitney test) ( Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the high complete necrosis rate of RFA, early tumor recurrence within one year, either local tumor recurrence or new tumor formation, can still be found. A series of studies discussed the factors for tumor recurrence including the tumor size, subcapsular lesion, operative procedure, underlying liver disease and alpha-fetoprotein (AFP) levels, but the results were not well documented [13][14][15]23] . The factors for the early tumor recurrence within one year were never discussed independently.…”
Section: Introductionmentioning
confidence: 99%
“…RFA has recently gained wide acceptance worldwide, mainly due to its relatively low level of invasiveness, ease of use and effectiveness (9,10). The incidence of local tumor progression of HCC reportedly ranges between 0.9 and 31.3% (5,9,(11)(12)(13)(14)(15)(16)(17)(18). Local tumor recurrence may occur due to untreated satellite lesions, which are too small to detect on imaging prior to RFA (19).…”
Section: Introductionmentioning
confidence: 99%
“…There es supporting R dard of care f be clearly seen n the surround latest improve erstandable tha HCC > 3 cm, t m [45,46] . In suc ve survival [44 ns that clinicia effusion and p eligible patient bility of incom in relation to mplete necrosis sular or within [43] [52,53] ) -accounting for 10%-15% of tumors [1] . In these scenarios, there is an increased risk of incomplete eradication and local tumor progression.…”
Section: Radiofreqmentioning
confidence: 99%
“…Drug-related adverse events were considered manageable, and no death related with toxicity was described [53,61] .…”
Section: Molecular Targeted Therapiesmentioning
confidence: 99%